Media Dakwah dalam Perspektif Tafsir Kementerian Agama RI (Kemenag RI) dan Ibnu Katsir - Prasongko, Wahyu Agung; Aisyah, Siti (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2024)
Explanation of the propagation media can be found in the Quran. Propagation media based on the interpretation of the Quran plays an important role in spreading the teachings of Islam and educating society about religious values. In the Quran, there are various perspectives of interpretation developed by scholars and commentators. Two of them are interpretations developed by the Ministry of Religious Affairs and Ibn Kathir's interpretation. The focus of this research is to examine the Quranic verses containing meanings as propagation media according to the interpretations of the Ministry of Religious Affairs and Ibn Kathir. This research uses descriptive qualitative research with the method of library research. The results show that based on the interpretations of the Ministry of Religious Affairs and Ibn Kathir, there are several interpretations of Quranic verses related to propagation media. Firstly, wasilah serves as a tool, means, or intermediary that facilitates propagators in achieving the goal, which is to convey the messages of Islamic propagation to the audience. Secondly, the Kaaba as the central point of propagation media. The Kaaba is the central point or qibla for all Muslims in the world (for prayer) and the center of worship for Muslims. The Kaaba is considered a propagation media because it involves activities related to Islamic law, such as circumambulation, prayer, pilgrimage, remembrance, and worship. Thirdly, the mosque as a propagation media has implications such as learning activities, performing prayers, and disseminating religious messages.